CRISPR-mediated loss of function analysis in cerebellar granule cells using in utero electroporation-based gene transfer - Feng, Weijun; Herbst, Lena; Lichter, Peter; Pfister, Stefan; Liu, Hai-Kun; Kawauchi, Daisuke (JoVE. Video journal, 2018)
Brain malformation is often caused by genetic mutations. Deciphering the mutations in patient-derived tissues has identified potential causative factors of the diseases. To validate the contribution of a dysfunction of the mutated genes to disease development, the generation of animal models carrying the mutations is one obvious approach. While germline genetically engineered mouse models (GEMMs) are popular biological tools and exhibit reproducible results, it is restricted by time and costs. Meanwhile, non-germline GEMMs often enable exploring gene function in a more feasible manner. Since some brain diseases (e.g., brain tumors) appear to result from somatic but not germline mutations, non-germline chimeric mouse models, in which normal and abnormal cells coexist, could be helpful for disease-relevant analysis. In this study, we report a method for the induction of CRISPR-mediated somatic mutations in the cerebellum. Specifically, we utilized conditional knock-in mice, in which Cas9 and GFP are chronically activated by the CAG (CMV enhancer/chicken ß-actin) promoter after Cre-mediated recombination of the genome. The self-designed single-guide RNAs (sgRNAs) and the Cre recombinase sequence, both encoded in a single plasmid construct, were delivered into cerebellar stem/progenitor cells at an embryonic stage using in utero electroporation. Consequently, transfected cells and their daughter cells were labeled with green fluorescent protein (GFP), thus facilitating further phenotypic analyses. Hence, this method is not only showing electroporation-based gene delivery into embryonic cerebellar cells but also proposing a novel quantitative approach to assess CRISPR-mediated loss-of-function phenotypes.
Enthält auch eine Versuchsbeschreibung in Textform
Gesehen am 11.05.2020
Wissenschaftlicher Film. Deutschland. 2018
Keywords: Film